The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1136/ard.2008.089375
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of a recombinant adenoassociated vector containing a tumour necrosis factor   antagonist gene in inflammatory arthritis: a phase 1 dose-escalation safety and tolerability study

Abstract: A single dose of intra-articular rAAV2-TNFR:Fc appears to be safe and well tolerated in subjects without concurrent systemic TNFalpha antagonist use. It is thus feasible to proceed with larger trials to further test the safety and efficacy of local TNFR:Fc gene transfer as a therapeutic modality for patients with inflammatory arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 27 publications
2
56
0
2
Order By: Relevance
“…19 Local gene transfer into the rheumatoid joints has been evaluated to bypass the inherited obstacle associated with delivery of therapeutic compounds. [20][21][22] Lentivirusmediated gene transfer has been shown to result in efficient expression of transgenes in synovial tissues. [21][22] As galectin-3 and galectin-1 appear to be positive and negative regulators, respectively, of inflammation and autoimmune responses, in this study we investigated the effects of galectin-3 gene silencing or galectin-1 overexpression mediated by lentiviral gene transfer in rats with CIA.…”
Section: Introductionmentioning
confidence: 99%
“…19 Local gene transfer into the rheumatoid joints has been evaluated to bypass the inherited obstacle associated with delivery of therapeutic compounds. [20][21][22] Lentivirusmediated gene transfer has been shown to result in efficient expression of transgenes in synovial tissues. [21][22] As galectin-3 and galectin-1 appear to be positive and negative regulators, respectively, of inflammation and autoimmune responses, in this study we investigated the effects of galectin-3 gene silencing or galectin-1 overexpression mediated by lentiviral gene transfer in rats with CIA.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, while the joints from control arthritic animals showed an intense inflammatory cellular infiltrates, pannus, and cartilage and bone degradation, the intraarticular injection of rAAV-TNFR:Fc decreased the cell infiltrates, reducing pro-inflammatory cytokines without detectable signs of cartilage degradation. TNFR:Fc RNA expression was detectable in joint tissue for a period of 3 months (monkey) to 1 year (rat) [98].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Preclinical studies of gene therapy for chondral and osteochondral regeneration reported in literature were on safety and efficacy of intra-articular administration of: (a) a 3:1 mixture of normal human chondrocytes and genetically modified human chondrocytes expressing TGF-β1 (TG-C, TissueGene, Inc., Rockville, USA) [81]; (b) a rAAV vector containing the cDNA for a human tumor necrosis factor receptor (TNFR) and immunoglobulin (IgG1) Fc fragment (TNFR:Fc) fusion gene (tgAAC94, Targeted Genetics Corporation, Seattle-Washington, USA) [98]; (c) genetically modified synovial cells (self-complementing recombinant AAV vector delivered in vitro) that express IL-1 Ra (scrAAV2.5IL-1Ra, Mayo Clinic, Rochester, Minnesota, USA). [60,97]; and (d) rAAV vector expressing human interferon-β (ART-I02, Arthrogen, Amsterdam, The Netherlands) [99,100].…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its impressive preclinical track record of efficacy and safety in animal models (as reviewed 5,6 ), progress in carrying out clinical trials has been painfully slow 4 . The literature contains only 2 small Phase I studies 3,4 and a report of 2 subjects who experienced symptomatic relief following gene transfer 7 .…”
mentioning
confidence: 99%